Diffusion-based time synchronization protocol for wireless sensor networks - SUN De-yun; SHEN Jie; LIU Hai-tao (Tongxin xuebao)
The lack of survivability in typical wireless sensor network （WSN） synchronization protocols leads to innova- tion in this hot topic, the diffusion-based time synchronization protocol （DTSP） makes nodes maintain themselves onto a global time consensus via local exchanges of timestamp information. DTSP cancels the synchronization root existing in most protocols which may cause security problems, by utilizing time-division and fault-tolerance technology, the surviv- ability is enhanced further. Appling DTSP with typical WSN nodes, experiments give excellent results in survivability, precision and scalability.